Improving Tax Understanding for MSMEs in the Waringinjaya Village, the Bojonggede Subdistrict, Bogor Regency - Atha Farras; Hikmahtul Hayati; Vinka Yuliana; Silvia Silvia; Iin Rosini; Ani Kusumaningsih (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the national economy, but still face challenges in terms of understanding and compliance with tax regulations. This Community Service Program is organized with the aim of improving the understanding and tax compliance levels of MSME actors in Waringinjaya Village, Bojonggede Subdistrict, Bogor Regency. The approach used includes preliminary surveys through field observations and interviews, tax education and socialization activities, technical training on tax calculation, as well as post-activity evaluation through the distribution of questionnaires and in-depth interviews. The material provided includes the basic concepts of tax obligations, types of taxes imposed on MSMEs, tax sanctions, and the implementation of Final Income Tax (PPh) for MSMEs based on Government Regulation Number 23 of 2018, which has been refined through Government Regulation Number 55 of 2022. The results of the program show a significant increase in the participants' understanding of tax obligations, with at least 80% of participants achieving a basic understanding of tax duties. Furthermore, MSME actors' awareness of the importance of financial record-keeping and systematic business administration has also improved. This program has had a positive impact on encouraging tax compliance based on awareness and strengthening the sustainable management capacity of MSMEs.